An investigation of access chemistry lecturers' practice of pedagogic content knowledge in chemical equilibrium in an access programme - Dharsey, Nadine (My University, 2009)
A qualitative case study was used to investigate the pedagogical content knowledge (PCK) in chemical equilibrium by two chemistry lecturers in an access programme at a technical university in Johannesburg. Since PCK has been identified as knowledge which is unique to teachers, the difference between the two lecturers’ teaching background, made for an interesting comparison. Mr Dhlamini was a post-graduate student who could have been described as an expert in the field of chemistry as he was completing his doctorate in chemistry and Mr Moerane who was an experienced teacher. Interviews as well as observations of the lecturers’ classroom practice were conducted to establish their interpretations and transformations of concepts in chemical equilibrium that make these concepts understandable to the student. The methodological tools used to document and portray the lecturers’ PCK in chemical equilibrium, used representations called Content Representation (CoRe) and Pedagogical and Professional – experience Repertoires (PaP-eRs). The CoRe elaborated on the teacher’s construction of content which framed the topic chemical equilibrium and each Pa-PeR, was a narrative derived from the interview before the lesson on chemical equilibrium was taught, the observation of two lessons, the lecturer’s reflections after the lesson and stimulated recall sessions. The use of the two tools was modified to suit the context of the study. A tailored model of PCK developed by Rollnick et al. (2008) was used to analyse and interpret data. The study showed that Mr Moerane’s PCK was far better developed (as shown by the overall strategy he developed and representations he used) while Mr Dhlamini, though a competent teacher, still had to develop a strategy, based on his understanding of practice.